Effects of caffeine intake on muscle strength and power: a systematic review and meta-analysis - Grgic, J.; Trexler, E. T.; Lazinica, B.; Pedisic, Z. (Journal of the International Society of Sports Nutrition, 2018)
Background: Caffeine is commonly used as an ergogenic aid. Literature about the effects of caffeine ingestion on muscle strength and power is equivocal. The aim of this systematic review and meta-analysis was to summarize results from individual studies on the effects of caffeine intake on muscle strength and power. Methods: A search through eight databases was performed to find studies on the effects of caffeine on: (i) maximal muscle strength measured using 1 repetition maximum tests; and (ii) muscle power assessed by tests of vertical jump. Meta-analyses of standardized mean differences (SMD) between placebo and caffeine trials from individual studies were conducted using the random effects model. Results: Ten studies on the strength outcome and ten studies on the power outcome met the inclusion criteria for the meta-analyses. Caffeine ingestion improved both strength (SMD = 0.20; 95% confidence interval [CI]: 0.03, 0.36; p = 0.023) and power (SMD = 0.17; 95% CI: 0.00, 0.34; p = 0.047). A subgroup analysis indicated that caffeine significantly improves upper (SMD = 0.21; 95% CI: 0.02, 0.39; p = 0.026) but not lower body strength (SMD = 0.15; 95% CI: -0.05, 0.34; p = 0.147). Conclusion: The meta-analyses showed significant ergogenic effects of caffeine ingestion on maximal muscle strength of upper body and muscle power. Future studies should more rigorously control the effectiveness of blinding. Due to the paucity of evidence, additional findings are needed in the female population and using different forms of caffeine, such as gum and gel.